2019
DOI: 10.1021/acs.nanolett.9b01708
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Deep-Brain Structural and Hemodynamic Multiphoton Microscopy Enabled by Quantum Dots

Abstract: Visualizing deep-brain vasculature and hemodynamics is key to understanding brain physiology and pathology. Among the various adopted imaging modalities, multiphoton microscopy (MPM) is well-known for its deep-brain structural and hemodynamic imaging capability. However, the largest imaging depth in MPM is limited by signal depletion in the deep brain. Here we demonstrate that quantum dots are an enabling material for significantly deeper structural and hemodynamic MPM in mouse brain in vivo. We characterized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
104
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 83 publications
(109 citation statements)
references
References 31 publications
5
104
0
Order By: Relevance
“…Wang et al, 2018). Large SBRs (> 40) were reported on 3-photon imaging of mouse brain vasculature at an imaging depth of greater than 5 attenuation lengths (Liu et al, 2019). However, for the depths beyond the white matter, our measured SBR of 3PM is lower than the theoretical prediction, which may be caused by the deterioration of the point spread function due to the strong aberration introduced by the white matter.…”
Section: Resultsmentioning
confidence: 99%
“…Wang et al, 2018). Large SBRs (> 40) were reported on 3-photon imaging of mouse brain vasculature at an imaging depth of greater than 5 attenuation lengths (Liu et al, 2019). However, for the depths beyond the white matter, our measured SBR of 3PM is lower than the theoretical prediction, which may be caused by the deterioration of the point spread function due to the strong aberration introduced by the white matter.…”
Section: Resultsmentioning
confidence: 99%
“…Here, an optical probe was used, since it could generate bright THG signals under the irradiation of 1560 nm fs laser, which was beneficial for evaluating the capability of the novel skull optical clearing window for NIR-II excited THG microscopy. Considering some tissues, such as dura mater and myelinated axons, can also arise strong THG signals [9,47], the VNSOCA has the potential to help realize unlabeled tissue imaging through the intact skull. In addition, although THG is a third-order nonlinear optical effect and three-photon fluorescence is a fifth-order nonlinear optical effect, the both signal intensity is proportional to the third power of the power density of the excitation light [40].…”
Section: Dicussionmentioning
confidence: 99%
“…The optical power on the sample can be continuously adjusted for measuring the power-dependent fluorescence signals, from which the nonlinear order can be identified through linear fitting on log scales. This system is also capable of measuring wavelength-dependent ησ 3 within the 1700nm window, 14,22 using sulforhodamine 101 (SR101) as the reference sample. 23 We note that the molar concentration of the FluoroMyelin Red stock solution (F34652, ThermoFisher) could not be disclosed by the manufacturer, so we could only measure the relative value of wavelength-dependent ησ 3 .…”
Section: Characterization Of 3-photon Property Of Fluoromyelin Redmentioning
confidence: 99%
“…In the realm of MPM, it has been demonstrated that 3-photon microscopy (3-PM) enables larger imaging depth compared with 2-PM in various biological tissues. 10,[12][13][14][15][16] The underlying physics is: (a) suppression of the surface background; (b) reduced tissue scattering due to long excitation wavelength at either the 1300-nm window or the 1700-nm window, manifesting in even through-the-skull brain imaging. [16][17][18] It can thus be expected that 3-PM is also a promising technique in imaging myelin in digital skin.…”
Section: Introductionmentioning
confidence: 99%